An approach for developing an interoperability mechanism between cloud providers. (1st January 2014) - Thabet, Meriem; Boufaida, Mahmoud; Kordon, Fabrice
Due to the presence of numerous cloud service providers, the requirement is emerging for interoperability between them so that companies can choose multiple suppliers to fit their needs. This paper provides an approach to address the problem of cloud interoperability. We aim at facilitating the collaboration among providers by proposing an architecture based on an agent society, to support and ensure the data portability and interoperability. For that, we define a two-phase migration protocol that enables data portability by permitting providers to exchange data regardless of their infrastructure, tools and platforms, according to a specific demand in order to satisfy companies' needs.